Implementation of the BALATEP Method (Build, Train and Apply) in the Development of River Tourism Areas in Ujung Teran Village - Gultom, Petrus Septian; Sitompul, Andreas; Naibaho, Aqnest Octaviani; Panggabean, Audrey; Ramdhani, Aulia; Wahyudi, Avghis Ageola; Setyowati, Cellyna; Augri, Fatiha; Veronica, Febi Yohana; Malem, Ingan Pusuh (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2023)
The BALATEP (Build, Train, and Apply) method is an effort to support the Desa Ujung Teran community in developing river tourism areas. The implementation of the BALATEP method includes several programs that are carried out regularly starting with observations reportiving people of Desa Ujung Teran, then conducting interviews with the local community, bridge repairs as well as cottage constructing and training the community Desa Ujung Teran, as well as assisting the community in carrying out activities people’s empowerment which is expected to have a long-term effect on people’s understanding in the development of river tourism areas in Desa Ujung Teran.